Actual Threat, Perceived Threat, and Authoritarianism: An Experimental Study. (10th June 2020) - Russo, Silvia; Roccato, Michele; Merlone, Ugo
Abstract: Archival, correlational, and experimental studies converge showing strong links between societal threat and authoritarianism. However, inconsistent with the social cognitive studies showing that our perception of the reality is systematically biased, the literature on the threat-authoritarianism relations has largely ignored the connection between the actual societal threat and its perception. In this study, we analyzed the relation between objective societal threat and authoritarians' perception of it, hypothesizing that authoritarians would tend to overestimate societal threat and that such overestimation would increase the endorsement of authoritarian attitudes and the preference for authoritarian political systems. Using an experimental approach, we studied the relations between right-wing authoritarianism (RWA), actual societal threat (manipulated as low vs. moderate), and perceived societal threat working with an Italian community sample ( N = 209, M age = 29.70, SD = 9.53, 64.1% women). Actual threat and RWA equally predicted participants' threat perception, while their interaction did not. In turn, threat perception further increased RWA and support to authoritarian political system. We discussed the results in terms of a vicious circle whereby authoritarians overestimate societal threat and such overestimation reinforces authoritarian attitudes.